2010
DOI: 10.1111/j.1365-3156.2010.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication of research findings: identifying the sources of information most important to national disease control officers in low- and middle-income countries

Abstract: SummaryMajor global health initiatives have brought new opportunities and increased funding for health programmes in countries tackling diseases, such as malaria, tuberculosis (TB), and HIV ⁄ AIDS. However, to deploy these investments effectively, health programme managers need much better access to research that assesses the advantages and disadvantages of different strategies. Communicating key findings via the sources of information that health officials use and trust helps to maximise the impact of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…This concurs with a previous study which reported that Asian health o cials preferred guidance from in-country sources. [31] Trust in the source is a major factor in the success of risk communication, with low trust resulting in decreased uptake. [32] When organizations are not transparent in communicating risks, their credibility is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with a previous study which reported that Asian health o cials preferred guidance from in-country sources. [31] Trust in the source is a major factor in the success of risk communication, with low trust resulting in decreased uptake. [32] When organizations are not transparent in communicating risks, their credibility is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the effect of the non-material aspects of health aid links results mainly from the transmission of knowledge and norms, which we will also refer to as communication. There is a body of evidence indicating that aid-related communication among officials across borders is a major source of inputs in domestic health policy making and, especially in the case of states with little endogenous research capacity, it is often the main source of inputs (Okuonzi & Macrae, 1995;Parkhurst et al, 2010;Sumner & Harpham, 2008;Trostle et al, 1999). The self-perception of officials in agencies such as the World Bank is often as providers of knowledge (Barnes et al, 2016).…”
Section: The Health Aid Network and Its Consequencesmentioning
confidence: 99%